Fashion design research - Mbeledogu, Ezinma (Laurence King Publishing, 2014)
Every fashion collection begins with research. But how do you start? How much should you do? How do you use that research? This book is designed to answer these questions and demystify the process for students. Illustrated throughout with inspirational photographs and images of good practice within student sketchbooks, the book begins with the basics of primary and secondary research sources and shows students how and where to gather information. Chapters on market, fabric and colour research are followed by the final chapter, which shows how to gather all the information together, understand it and use it in a process known as triangulation. Additionally, case studies from a wide range of international designers showcase different working methods.